Entomophagy and allergies: a study of the prevalence of entomophagy and related allergies in a population living in North-Eastern Thailand. (4th July 2018) - Taylor, Geoffrey; Wang, Nanxi
Abstract: As the population of the world grows, so does the need for sustainable food. Insect farming and consumption can help ease the burden of supply from other more conventional food sources. This article investigates the prevalence of allergic reactions caused by consuming edible insects. The investigation was conducted in the North-Eastern or the Isan region of Thailand, in an area where insect consumption or entomophagy is a common practice. Information concerning insect consumption and allergic reactions were gathered from multiple sources in four locations: Nongki, Nang Rong, Nong Bun Mak and Nakhon Ratchasima. The survey included questions about eating habits in relation to insects, other known food allergies and presented a list of symptoms the participants may have experienced. The results from 2500 respondents were surprising in that the prevalence of allergic reactions caused by consuming edible insects was much higher than expected. In the Isan region approximately 7.4% of people experienced an adverse reaction indicative of an edible-insect allergy and 14.7% of people experienced multiple adverse reactions indicative of an edible-insect allergy. Furthermore, approximately 46.2% of people that already suffer from a known food-based allergy also experienced symptoms indicative of an allergic reaction after insect consumption. The most common symptoms appear to be gastro-intestinal (diarrhoea and vomiting). In conclusion, the allergy aspect of entomophagy is a serious issue and has the potential to adversely affect the future of entomophagy, especially in introducing the concept to western cultures. Although preliminary in its findings, this article hopes to ignite further research into the topic in order to fully understand the implications and role that edible insects can have on the immune system.